2021
DOI: 10.1108/itse-08-2020-0137
|View full text |Cite
|
Sign up to set email alerts
|

Flipped Classroom model before and during COVID-19: using technology to develop 21st century skills

Abstract: Purpose The confidence placed in the use of technology and other computing resources is an important support for the deep transformation toward processes of very high quality teaching-learning based on active learning. This paper aims to present and describe a higher education experience with Flipped Learning before and during the transformation of education due to the COVID-19 pandemic. In addition, the study analyzes the effectiveness perceived by university students of Flipped Learning for the development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 44 publications
4
55
0
5
Order By: Relevance
“…Thus, this new and unexpected situation did not especially affect their interest in the FC model, and they were willing to participate and collaborate to do better in the future. As the comparative research shows (Latorre-Cosculluela et al, 2021), respondents were more willing to actively participate in the FC model than to be passive recipients of the information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, this new and unexpected situation did not especially affect their interest in the FC model, and they were willing to participate and collaborate to do better in the future. As the comparative research shows (Latorre-Cosculluela et al, 2021), respondents were more willing to actively participate in the FC model than to be passive recipients of the information.…”
Section: Discussionmentioning
confidence: 99%
“…Chick et al (2020) offer several solutions to mitigate the risk of virus spread, including the FC model, teleconferencing, and online practice, with positive outcomes, as participants were satisfied with the format and were interested in continuing to learn without regularly attending face-to-face lectures. Comparative research was conducted by Latorre-Cosculluela et al (2021), who concluded that participants were inclined to take a more active role in their own learning process by developing 21stcentury skills (e.g., critical thinking or creativity) under the FC model rather than passively listening to direct instruction. In this regard, other studies highlighted the relevance of videos, recorded lectures, and group discussions, among other digital resources, to foster discussions, stimulate student learning and divert attention away from the current disruption caused by the pandemic (Agarwal and Kaushik, 2020;Guraya, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In this experience, an alternative to traditional engineering teaching has been implemented, developing activities based on the PBL model and adopting a CRS to improve communication in the classroom. The design of the activities took into consideration some learning difficulties and the related teaching proposals and advice identified by the research on the field [34,[49][50][51][52]. In this regard, noticeable differences resulted in the suitability of web-based methods between undergraduate courses and Master's courses, and between fundamental and technological modules.…”
Section: Resultsmentioning
confidence: 99%
“…Diverse studies focused on evaluating the readiness of lecturers and the feasibility of LMS [40,41], others on collecting students' perceptions [42][43][44], on analyzing the impact of the online format on studying at home [44,45], on learning achievements [46,47], and on the efficiency of flipped teaching methods [44,[48][49][50][51][52]]. It appears that blended learning methods have suffered less than other teaching approaches during this sudden shift to remote teaching [51].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation